2021
DOI: 10.1002/pat.5355
|View full text |Cite
|
Sign up to set email alerts
|

The role of amphiphilic chitosan in hybrid nanocellulose–reinforced polylactic acid biocomposite

Abstract: The blending of hydrophilic materials with hydrophobic polymers has been reported with agglomeration due to their functional group immiscibility properties. In this study, the properties of PLA/CNF biocomposite were enhanced with amphiphilic chitosan produced by a substitution reaction. The substitution reaction was studied with FT‐IR analysis. The amphiphilic chitosan was used as part of the matrix PLA/chitosan and reinforced with CNF to obtain PLA/chitosan/CNF biocomposite using combined melt extrusion and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Furthermore, the swelling thickness of PLA/chitin/CNF (i.e., P90101, P90103, and P90105) increased with the addition of CNF, which can be explained by the hydrophilic nature of CNF. Generally, swelling thickness observed in this study depended on the polymer mix's nature and the porosity (the voids or space) between the polymer mix molecules [51]. The value of the percentage thickness of swelling was relatively low, which shows that the biocomposite has low porosity and is highly resistant to water [53].…”
Section: The Physical Properties Of Bamboo and Commercial Cnf-reinforced Pla/chitin Bionanocompositesmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the swelling thickness of PLA/chitin/CNF (i.e., P90101, P90103, and P90105) increased with the addition of CNF, which can be explained by the hydrophilic nature of CNF. Generally, swelling thickness observed in this study depended on the polymer mix's nature and the porosity (the voids or space) between the polymer mix molecules [51]. The value of the percentage thickness of swelling was relatively low, which shows that the biocomposite has low porosity and is highly resistant to water [53].…”
Section: The Physical Properties Of Bamboo and Commercial Cnf-reinforced Pla/chitin Bionanocompositesmentioning
confidence: 62%
“…The thickness of the PLA/chitin and PLA/chitin/CNF increased compared with that of the neat PLA. Neat PLA has a lower swelling thickness [51]. The PLA-chitin composite increase compares to that of neat PLA.…”
Section: The Physical Properties Of Bamboo and Commercial Cnf-reinforced Pla/chitin Bionanocompositesmentioning
confidence: 86%
“…In the XRD test of RW and biocomposites (Figure e), the types of fiber crystals in the samples show no changes after extraction, alkali treatment, and hot molding. The major peaks were assigned at 2θ = 18.4, 22, and 34.8°, which correspond to the reflections of (101), (002), and (004) . The (002) reflection was the main crystallization peak of cellulose I.…”
Section: Resultsmentioning
confidence: 98%
“…The major peaks were assigned at 2θ = 18.4, 22, and 34.8°, which correspond to the reflections of (101), (002), and (004). 79 The (002) reflection was the main crystallization peak of cellulose I. The fiber crystallinity index (CrI) of the sample calculated by the Segal empirical equation shows that the fiber crystallinity of HMRW was the lowest, while HMPW shows the highest value.…”
Section: Micromorphology Investigationmentioning
confidence: 98%
“…It is commercially available and could be considered as an option for recombination with PLA to reduce the cost of novel composites (Claro et al 2016;Kanani et al 2021;Elsawy et al 2023;Kamaludin et al 2023). Previous research on PLA/chitin bio-composites showed that chitosan could be blended with PLA to improve its mechanical properties (Nasution et al 2021;Rizal et al 2021). Claro et al 2016 have obtained PLA-chitosan blends by mixing PLA pellets with either 1 to 2 mm chitosan granules without the addition of plasticizers or additives to synthesize composites with improved thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%